(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Body Mapping has been used for thousands of years by people who want to achieve a better understanding of themselves, their bodies and the world they live in. Artist Jane Solomon and psychologist Jonathan Morgan transformed Body Mapping for the “Long Life Project”, during the Médecins Sans Frontières (MSF) roll-out of antiretrovirals in Khayelitsha township, South Africa in 2001. Body mapping enables participants to tell their stories in the face of intense HIV/AIDS stigma. We adapted Body Mapping for the Women, Art and Criminalizaton of HIV Non-Disclosure (WATCH) study, a community arts based research (CBR) approach to better understand the impact that Canadian laws criminalizing HIV non-disclosure have on women living with HIV. Our national team includes women living with HIV, service providers, and researchers. This reflection illustrates our collective and iterative process of learning, teaching and doing body mapping workshops with women living with HIV in Canada. We share our experiences of coming to Body Mapping as an arts-based approach to CBR, how our roles as researchers stretched to include community-based education, advocacy, and group facilitation, and how we embodied the artist-researcher identity as we disseminate our research in ways that actively engage the general public on laws criminalizing HIV nondisclosure laws vis-à-vis Body Mapping galleries.